Students’ Interest In Learning English At The Third Semester Students Of Health Faculty Of Mega Buana University - Tri Endar Yogi Setiadi Saputra (Perkumpulan Dosen Muslim Indonesia - Sulawesi Selatan, 2023)
Students’ Interest in Learning English at the Third Semester Student of Health Faculty of Mega Buana University. How the students’ interest in learning English at the third semester students of Health Faculty of Mega Buana University? The objective of the research was found out the students’ interest in learning English at the third semester students of Health Faculty of Mega Buana University. The researcher applied purposive sampling technique in getting data because the sample data sources need special consideration. Special consideration here by taking the students that have good mean score in the class especially in English score. Based on the purposive sampling technique, the researcher’s subjects are 8 from 73 students in the classroom in Public Health Study Program Health Faculty. Based on the result the most important is their interest in learning English. They gave the positive response. For example their interest in learning English is very good, very interesting, very big and very strong. This situation can be seen from the observation and the result of the interview. They had big interest and big motivation when learn in the class they are always present. They said that English is very important especially in their study program